Innovative Therapeutic Approaches in Primary Cutaneous B Cell Lymphoma - Lang, Claudia C. V.; Ramelyte, Egle; Dummer, Reinhard (Frontiers in Oncology, 2020)
Background: Primary cutaneous B-cell lymphomas (pCBCL) include an infrequent group of non-Hodgkin lymphomas that are limited to skin sites at the time of diagnosis. They comprise roughly 20–25% of all cutaneous lymphomas and are subdivided into primary cutaneous marginal zone lymphoma (PCMZL), primary cutaneous follicle center lymphoma (PCFCL), and primary cutaneous diffuse large cell B cell lymphoma, leg type (PCDLCBCL, LT). The first two show a rather indolent course while PCDLCBCL, LT carries a worse prognosis. Intravascular large cell B-cell lymphoma is the most infrequent subtype, and its therapy is not covered in this review. Topical Therapy: For solitary, single-site PCMZL and PCFCL, several topical treatment options exist. They include, but are not limited to, excision, radiotherapy, and intralesional therapies, discussed in this review. However, in selected cases, even “watchful waiting” is reasonable. Systemic Therapy: Indolent types of pCBCL rarely require systemic treatment. However, in extended cases and more importantly DLCBCL, LT, systemic treatment is the first choice. Monoclonal anti-CD20-antibody rituximab is often used as monotherapy in PCMZL and PCFCL or combined with chemotherapy in PCDLBCL, LT. Newer options are monoclonal anti-CD40 antibody dacetuzumab, anti-PD-1 and anti-PD-L1 checkpoint inhibitors, and Bruton tyrosine kinase inhibitors. Conclusion: Indolent pCBCL are treated with a risk-adapted strategy using intralesional steroids, RT, and interferon-α as first-line treatments. Relapsing cases may profit from rituximab. In aggressive PCDLCBCL, LT, rituximab with polychemotherapy is recommended. Innovative therapies include intralesional oncolytic virotherapy, systemic monoclonal antibodies, and small molecules.